Astromeric reduction of CFHTLS-VW IMAGES: Preliminary Results - Bustos Fierro, Iván Heriberto (2015)
In this paper we show the results of the astrometric reduction of a set of images taken on the ecliptic region that belong to the CFHTLS-VW collection. We discuss the choice of the model used for the reduction and the criteria for the selection of the reference stars. Images of two fields widely separated in the sky that were taken with different filters were reduced in order to discuss the maximum achievable astrometric accuracy with the choice referred above. The final goal of this work is to build a deep catalog providing information on astrometry, photometry and object classification of the sources detected in the ecliptical zone.